High-Gain Optical Injection Locking Amplifier in Phase-Coherent Optical Frequency Transmission - Zitong Feng; Xi Zhang; Rui Wu; Yanguang Sun; Fang Wei; Fei Yang; Youzhen Gui; Haiwen Cai (IEEE Photonics Journal)
Optical amplification, which is necessary for extending the distance of optical frequency transfer, has a significant impact on the transmission performance. In this paper, we propose a high-gain optical injection locking amplifier (OILA) with low phase noise based on an optical injection phase-locked loop for the phase-coherent optical frequency transmission. The high-gain OILA can provide more than 75-dB gain and ensure that the input carrier frequency fractional stability can reach 8.2 × 10−20 at an averaging time of over 100 s. We then transfer a commercial narrow-linewidth laser over a 220-km fiber link with only one amplification step placed at the remote end. After eliminating the noise induced in the fiber link, the fractional frequency instability of the transferred frequency can reach 9.0 × 10−16 at 1 s and 7.1 × 10−20 at 20 000 s.